2022
DOI: 10.14338/ijpt-22-00013.1
|View full text |Cite
|
Sign up to set email alerts
|

Proton Arc Therapy vs Interstitial HDR Brachytherapy in Gynecologic Cancer with Parametrial/pelvic Side Wall Extension

Abstract: Purpose To investigate whether volumetric-modulated proton arc therapy (VPAT) plans generate comparable doses to organs at risk (OARs) compared with interstitial high–dose-rate (iHDR) brachytherapy for patients with gynecologic cancer with disease extension to parametrial/pelvic side wall, who are not eligible for the aggressive procedure. Materials and Methods VPAT delivers proton arc beams by modulated energies at the beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Proton arc therapy benefits include a reduced integral dose and improved robustness of target coverage in comparison to photon arc radiotherapy; however, challenges of this technique include changing energies during treatment delivery with gantry motion. 24 FLASH therapy is a developing radiotherapy technique in electron and photon radiotherapy, which involves utilising high dose rates in order to deliver high dose per fraction (over forty gray per fraction). 25 Pre-clinical FLASH studies have demonstrated significantly reduced radiation side effects whilst achieving disease control, therefore exploiting the physical properties of protons may prove advantageous due to more conformal high dose to target volumes achieved in comparison to photons.…”
Section: R Baileymentioning
confidence: 99%
“…Proton arc therapy benefits include a reduced integral dose and improved robustness of target coverage in comparison to photon arc radiotherapy; however, challenges of this technique include changing energies during treatment delivery with gantry motion. 24 FLASH therapy is a developing radiotherapy technique in electron and photon radiotherapy, which involves utilising high dose rates in order to deliver high dose per fraction (over forty gray per fraction). 25 Pre-clinical FLASH studies have demonstrated significantly reduced radiation side effects whilst achieving disease control, therefore exploiting the physical properties of protons may prove advantageous due to more conformal high dose to target volumes achieved in comparison to photons.…”
Section: R Baileymentioning
confidence: 99%